Pozzolanic Reactivity and the Influence of Rice Husk Ash on Early-Age Autogenous Shrinkage of Concrete - Amin, Muhammad Nasir; Hissan, Syed; Shahzada, Khan; Khan, Kaffayatullah; Bibi, Tayyaba (Frontiers in Materials, 2019)
In this study, the role of a locally available rice husk ash (RHA) in reducing early-age shrinkage of high performance concrete (HPC) after evaluating its pozzolanic reactivity was evaluated. The X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analyses were performed after burning rice husk to 700 and 950 oC. Presence of relatively high deposits of amorphous siliceous phases in RHA at 700 oC indicated its pozzolanic potential. Subsequently, this RHA was ground to desired fineness, followed by sieving through sieve No. 200. Eventually, the fine RHA was used as a substitute of cement in different percentages (10, 15 and 20%) to evaluate its influence in mitigating autogenous shrinkage in concrete. Prismatic concrete beams (100 mm x 100 mm x 800 mm) were cast to measure autogenous shrinkage along with cylinders (150 mm dia. x 300 mm height) to test compressive strength of concrete. The results indicated a slight increase in compression strength with addition of 10% RHA, which however, reversed and slightly reduced in concretes containing 15 and 20% RHA. Unlike strength results, the trend of autogenous shrinkage was rather uniform as the rate as well as the amount of early-age autogenous shrinkage continued to decrease with increasing percentage of RHA. Moreover, despite of reduced rate during first 24 hours, thereafter, the effect of 20% RHA on further reduction of autogenous shrinkage was insignificant and ended up only slightly lesser than the 15% RHA concrete at 7 days. Finally, the control cement sand mortar and mortar containing 15% RHA were cast to further validate the pozzolanic reactivity of RHA through scanning electron microscopy (SEM), EDX and thermogravimetric analysis (TGA) tests. An observation of reduced amount of calcium hydroxide (Ca(OH)2) in RHA mortar samples indicating its excellent pozzolanic potential when used as a partial substitute of cement in HPC.